Family correlates of behavioral problems among adolescents in Rwanda. - Eugene Harerimana; Jean d'Amour Muziki; Eric Nshimyumuremyi; Thaoussi Uwera; Augustin Nshimiyimana; Jean Mutabaruka (PLoS ONE)
Background Globally, 20% of adolescents exhibit behavioral problems. Behavioral problems are associated with individual and environmental factors. However, little is known about the contribution of the nuclear family to the development of behavioral problems in adolescents from sub-Saharan Africa. This study aimed to explore family-based correlates influencing behavioral problems among adolescents in Rwanda. Methods With an institutional-based cross-sectional study design, a convenience sample of 158 participants {107 males and 51 females; Mean age (M) = 16.96, Standard Deviation (SD) = 1.86; age ranging from 13 to 23 years} was selected in secondary schools in the Nyarugenge district. Participants filled out Behavioral Problems Scale (BPS), Child and Adolescent Trauma Screen (CATS), University of California, Los Angeles Loneliness Scale (UCLA Loneliness Scale), Multidimensionality of Perceived Social Support Scale (MSPSS), Multidimensional Neglectful Behavior Scale (MNBS), and Paediatric Quality of Life Enjoyment and Satisfaction Questionnaire (PQ-LES-Q) to record pertinent scores. Socio-demographic information was also collected. SPSS version 24 was used for statistical analysis. Results Females exhibited more behavioral problems than males. Child and adolescent trauma (β = 0.705, t = 8.21, p < .001) and neglect (β = 0.147 t = 2.15, p < .05) were two significant family correlates in our sample. Poor quality of life enjoyment and satisfaction, loneliness, and poor parental perceived social support were not identified as family-based factors that influence behavioral problems in our sample. Conclusions Results highlighted the importance of implementing family and community-based interventions to sustain family well-being, change parenting behaviors, and help children and adolescents adopt positive behaviors.